Analisis faktor sumber daya dalam implementasi kebijakan aplikasi e visum penyuluh keluarga berencana di Kabupaten Grobogan - janana badra (Universitas Muhammadiyah Mataram, 2023)
The e visum application is an application to measure the performance of family planning concelor. In implementing the policy of using the e visum application 4th generation in Grobogan Regency, there are several factors that are driving factors and inhibiting factors. One of these factors is the resource factor. This study aims to describe and analyze resource factors as driving factors and inhibiting factors for the successful implementation of e visum applications 4th generation in Grobogan regency. Data analysis was carried out through data condensation, data display and drawing conclusions. The results showed that the ability of resources, especially the ability of family planning counselors to operate computers must be improved. Need to improve the quality of the server so that the application can run smoothly. It is necessary to appoint staff and provide special incentives for e visum application managers.